A Kinetic Model Considering Catalyst Deactivation for Methanol-to-Dimethyl Ether on a Biomass-Derived Zr/P-Carbon Catalyst - Torres-Liñán, Javier; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (IOAP-MDPI, 2022)
A Zr-loaded P-containing biomass-derived activated carbon (ACPZr) has been tested for methanol dehydration between 450 and 550 °C. At earlier stages, methanol conversion was complete, and the reaction product was mainly dimethyl ether (DME), although coke, methane, hydrogen and CO were also observed to a lesser extent. The catalyst was slowly deactivated with time-on-stream (TOS), but maintained a high selectivity to DME (>80%), with a higher yield to this product than 20% for more than 24 h at 500 °C. A kinetic model was developed for methanol dehydration reaction, which included the effect of the inhibition of water and the deactivation of the catalyst by coke. The study of stoichiometric rates pointed out that coke could be produced through a formaldehyde intermediate, which might, alternatively, decompose into CO and H2. On the other hand, the presence of 10% water in the feed did not affect the rate of coke formation, but produced a reduction of 50% in the DME yield, suggesting a reversible competitive adsorption of water. A Langmuir–Hinshelwood reaction mechanism was used to develop a kinetic model that considered the deactivation of the catalyst. Activation energy values of 65 and 51 kJ/mol were obtained for DME and methane production in the temperature range from 450 °C to 550 °C. On the other hand, coke formation as a function of time on stream (TOS) was also modelled and used as the input for the deactivation function of the model, which allowed for the successful prediction of the DME, CH4 and CO yields in the whole evaluated TOS interval.
Keywords: Methanol dehydration; Dimethyl ether; Biomass-derived carbon; Zirconium phosphate; kinetic modelling; Deactivation